Milnor versus Tjurina - Ploski, Arkadiusz (2023)
This note, based on the talk given by the author at the Conference in Analytic and Algebraic Geometry, Lodź 2023, is an overview of the results on the invariants of hypersurface singularities in positive characteristic.